2005
DOI: 10.1038/sj.ijir.3901334
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone therapy in women: a review

Abstract: Female sexual dysfunction is a complex problem with multiple overlapping etiologies. Androgens play an important role in healthy female sexual function, especially in stimulating sexual interest and in maintaining desire. There are a multitude of reasons why women can have low androgen levels with the most common reasons being age, oophorectomy and the use of oral estrogens. Symptoms of androgen insufficiency include absent or greatly diminished sexual motivation and/or desire, that is, libido, persistent unex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
2
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 57 publications
1
57
2
2
Order By: Relevance
“…We also analyzed current psychiatric disorders within the preceding month for depressive disorder and anxiety disorders (i.e., social phobia, panic disorder and/or agoraphobia, and generalized anxiety disorder). The total score of the Inventory of Depressive Symptomatology Self Report (IDS-SR) was used to assess overall depression severity, [60] and subdivided into five severity groups, i.e., low (total score 0-13), mild (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), moderate (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38), severe (39)(40)(41)(42)(43)(44)(45)(46)(47)(48), and very severe . Item 22 (i.e., interest in sex) from the IDS-SR was analyzed separately as an internal validation of the salivary testosterone assessment, that was rated on a four-point scale: 0 (i.e., usual interest), 1 (i.e., somewhat less interest or pleasure), 2 (i.e., little interest or pleasure), and 3 (i.e., no interest or pleasure).…”
Section: Assessment Of Psychopathology and Antidepressant Usementioning
confidence: 99%
See 1 more Smart Citation
“…We also analyzed current psychiatric disorders within the preceding month for depressive disorder and anxiety disorders (i.e., social phobia, panic disorder and/or agoraphobia, and generalized anxiety disorder). The total score of the Inventory of Depressive Symptomatology Self Report (IDS-SR) was used to assess overall depression severity, [60] and subdivided into five severity groups, i.e., low (total score 0-13), mild (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), moderate (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38), severe (39)(40)(41)(42)(43)(44)(45)(46)(47)(48), and very severe . Item 22 (i.e., interest in sex) from the IDS-SR was analyzed separately as an internal validation of the salivary testosterone assessment, that was rated on a four-point scale: 0 (i.e., usual interest), 1 (i.e., somewhat less interest or pleasure), 2 (i.e., little interest or pleasure), and 3 (i.e., no interest or pleasure).…”
Section: Assessment Of Psychopathology and Antidepressant Usementioning
confidence: 99%
“…The brain contains receptors for testosterone [16][17][18][19], and is capable of synthesizing and metabolizing testosterone to, for instance, estradiol [20][21][22]. In some studies, a low androgen status has been associated with symptoms of fatigue, irritability, dysphoria, declining vigor, low vitality, sexual dysfunction in men [23][24][25][26] and women [27], and an increased risk of depressive symptoms and depression in most [28][29][30] but not all studies [31,32]. Findings were mixed, however, as several other epidemiological studies did not show or showed non-linear relationships between testosterone levels and depressive symptoms [33].…”
Section: Introductionmentioning
confidence: 99%
“…Most clinical trials in postmenopausal women with decreased interest in sexual activities have clearly demonstrated that the addition of testosterone to estrogen significantly improved multiple facets of sexual functioning, including libido, arousal, frequency and satisfaction. 2 No case reports have been published yet explaining the effect of testosterone in a fragile X carrier who behaves as a normal XX female, with few exceptions like premature ovarian failure, which is found in 28% of female fragile X premutation carriers. 3 We have tried to explain a one and one-half year followup in treating hypoactive sexual desire disorder with this disease.…”
Section: Discussionmentioning
confidence: 99%
“…There are a multitude of reasons why women can have low androgen levels, with the most common reasons being age, oophorectomy, hypothalamic-pituitary abnormalities, adrenal insufficiency, glucocorticoid therapy and the use of exogenous estrogens. 1,2 In a fragile X carrier state, oral contraceptive pills and premature ovarian failures can lead to low androgen levels. Symptoms of androgen insufficiency include absent or greatly diminished sexual motivation and/or desire (or libido), persistent unexplainable fatigue or lack of energy, and a lack of sense of well-being.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, sexual behaviour of females may enhance the opportunity for engaging in extra-pair copulations; for example, during the fertile period, female humans (Homo sapiens) have greater desire or interest in extra-pair mates (e.g., Gangestad et al, 2002;Gangestad et al, 2005). Experimentally elevating T concentrations increases aggressive behaviour in female birds (Zysling et al, 2006;Sandell, 2007;Rosvall, 2013) and sexual interest, libido and behaviour in humans (reviewed in Bolour and Braunstein, 2005); however, studies investigating whether elevated T mediates extra-pair copulation behaviour in female birds have produced mixed results. T-treated female dark-eyed juncos (Junco hyemalis) did not differ from control females in the proportion of extra-pair offspring in their nests (Gerlach and Ketterson, 2013), whereas extra-pair paternity was lower for T-treated female spotless starlings (Sturnus unicolor) and blue tits (Cyanistes caeruleus) when compared to control females (García-Vigón et al, 2008;de Jong, 2013, respectively).…”
Section: Introductionmentioning
confidence: 99%